2001
DOI: 10.1097/00002030-200110190-00023
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection with HTLV-1 is associated with a shorter survival time for HIV-1-infected patients in Bahia, Brazil

Abstract: Co-infection with HTLV-1 reaches 20% among patients infected by HIV-1 in Bahia, Brazil. To evaluate its impact on survival, we conducted a retrospective, case-control study involving 198 patients (63 cases). Co-infection was associated with parenteral exposure (P = 0.0001) and female sex (P = 0.02). Co-infected patients had a shorter mean survival (1849 days) than controls (2430 days, P = 0.001), regardless of sex or baseline CD4 cell count. In Bahia, Brazil, co-infection with HIV-1 and HTLV-1 is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 6 publications
3
53
0
2
Order By: Relevance
“…HTLV-I shares a similar tropism with HIV and has indeed been suggested to accelerate progression of HIV. 16 However, syphilis did not follow this pattern because it only affected the activated T cell pool. KSHV on the other hand decreased naive CD4 T cells without affecting T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…HTLV-I shares a similar tropism with HIV and has indeed been suggested to accelerate progression of HIV. 16 However, syphilis did not follow this pattern because it only affected the activated T cell pool. KSHV on the other hand decreased naive CD4 T cells without affecting T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have evaluated the effect of HTLV-I infection on survival of HIV patients 4,6,12,16,18,22 . Most of them suggested that HIV/HTLV-I co-infection shortens the survival of these patients 6,12,16,18,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of them suggested that HIV/HTLV-I co-infection shortens the survival of these patients 6,12,16,18,22 . In contrast, a recent longitudinal retrospective study showed that the HTLV-I infection in persons with HIV was not associated with a shorter survival 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations